The genus Coleobonzia declared synonymous with Neobonzia Smiley, 1992 (Bdelloidea: Cunaxidae: Coleoscirinae) - Heyer, Jacob Den (Zootaxa, 2011)
Recent investigations into the status of Smiley’s (1992) subfamily Neobonzinae, as well as the genus Neobonzia Smiley, 1992, has led to a re-evalution of this taxon.